Biodegradable microplastics induce profound changes in lettuce (Lactuca sativa) defense mechanisms and to some extent deteriorate growth traits - Adamczyk, Sylwia; Zantis, Laura J.; van Loon, Sam; van Gestel, Cornelis A.M.; Bosker, Thijs; Hurley, Rachel; Nizzetto, Luca; Adamczyk, Bartosz; Velmala, Sannakajsa (Elsevier, 2024)
The development of agricultural technologies has intensified the use of plastic in this sector. Products of plastic degradation, such as microplastics (MPs), potentially threaten living organisms, biodiversity and agricultural ecosystem functioning. Thus, biodegradable plastic materials have been introduced to agriculture. However, the effects of biodegradable plastic substitutes on soil ecosystems are even less known than those of traditional ones. Here, we studied the effects of environmentally relevant concentrations of MPs prepared from a biodegradable plastic (a starch-polybutylene adipate terephthalate blend, PBAT-BD-MPs) on the growth and defense mechanisms of lettuce (Lactuca sativa) in CLIMECS system (CLImatic Manipulation of ECosystem Samples). PBAT-BD-MPs in the highest concentrations negatively affected some traits of growth, i.e., dry weight percentage, specific leaf area, and both C and N contents. We observed more profound changes in plant physiology and biochemistry, as PBAT-BD-MPs decreased chlorophyll content and triggered a concerted response of plant defense mechanisms against oxidative stress. In conclusion, exposure to PBAT-BD-MPs induced plant oxidative stress and activated plant defense mechanisms, leading to oxidative homeostasis that sustained plant growth and functioning. Our study highlights the need for in-depth understanding of the effect of bioplastics on plants.
Keywords: CLIMECS system; starch-polybutylene adipate terephthalate; PBAT; lipid peroxidation; total phenolic content; salicylic acid